2023
DOI: 10.3389/fimmu.2023.1172993
|View full text |Cite
|
Sign up to set email alerts
|

Understanding humoral immunity and multiple sclerosis severity in Black, and Latinx patients

Abstract: People identified with Black/African American or Hispanic/Latinx ethnicity are more likely to exhibit a more severe multiple sclerosis disease course relative to those who identify as White. While social determinants of health account for some of this discordant severity, investigation into contributing immunobiology remains sparse. The limited immunologic data stands in stark contrast to the volume of clinical studies describing ethnicity-associated discordant presentation, and to advancement made in our unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 151 publications
(73 reference statements)
0
13
0
Order By: Relevance
“…There is mounting evidence that when the diagnosis of MS is made close to the biological onset, after a clinical event and treated with appropriate medications, there is a greater impact on the trajectory of patients who otherwise will accumulate clinical and subclinical disease with pathological progression. Despite some uncertainties due to a lack of prospective trials, there is a realization that early intervention with medications tailored to a risk assessment for progression has changed the trajectory of MS. 7 More work remains to be done since there is a growing understanding that patients with the highest risk of progression of disability are those with significant SDOH barriers, including African American, Hispanics, and rural patients in neurology deserts. 37 Here, we built a proactive educational tool to educate students based on consensus signs for early awareness in MS, based on current evidence, which can be used in bilingual settings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is mounting evidence that when the diagnosis of MS is made close to the biological onset, after a clinical event and treated with appropriate medications, there is a greater impact on the trajectory of patients who otherwise will accumulate clinical and subclinical disease with pathological progression. Despite some uncertainties due to a lack of prospective trials, there is a realization that early intervention with medications tailored to a risk assessment for progression has changed the trajectory of MS. 7 More work remains to be done since there is a growing understanding that patients with the highest risk of progression of disability are those with significant SDOH barriers, including African American, Hispanics, and rural patients in neurology deserts. 37 Here, we built a proactive educational tool to educate students based on consensus signs for early awareness in MS, based on current evidence, which can be used in bilingual settings.…”
Section: Discussionmentioning
confidence: 99%
“…More notably, early awareness can increase the detection of MS since there is heterogeneity in clinical presentations and disease trajectories are worse in Hispanic and African American patients and not all patients will follow a predetermined path. 7 However, there are established clinical elements accompanied by risk factors that can help identify people with the highest risk of MS, including those with high-risk social determinants of health (SDOH) elements that can delay the diagnosis; therefore, it is crucial to increase awareness in these populations. 8…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While disparities are likely driven by SDoH, possible biologic differences across peoples should not be ignored. Four studies included in a recent review showed racial differences in antibody response with Black individuals having higher CNS antibody burden and intrathecal immunoglobulin response compared to White people with MS [22 ▪ ]. While the significance of these differences is not certain, studies have shown relationships between IgG index or intrathecal antibody-secreting cells and grey matter atrophy or enhancing lesions in MS patients [15,22 ▪ ].…”
Section: Implicating Social Determinants Of Health In Worse Outcomesmentioning
confidence: 99%